Interfacial stability of compatibilizers dictated by the thermodynamic interactions in an immiscible system and the effects of micelles on the crystallization of PLLA. Issue 2 (20th January 2020) - Dong, Wenyong; He, Meifeng; Ren, Fanglu; Li, Yongjin; Hanada, Takeshi; Lee, Sungdoke; Hakukawa, Hideki; Yamahira, Naohiro; Horiuchi, Shin
ABSTRACT: Poly(L‐lactic acid) (PLLA) is blended with three acrylonitrile‐butadiene‐styrene (ABS) materials and compatibilized by a kind of poly(methyl methacrylate) (PMMA)‐type reactive comb (RC) polymer (RC). The compatibilization efficiency is found to be dictated by the thermodynamic interactions between PMMA‐type compatibilizers and ABS materials. For one type of ABS, which is composed of methyl methacrylate (MMA), styrene (St), acrylonitrile (AN), and butadiene (BD), the MMA component of ABS is able to strengthen the interaction between the PMMA‐type compatibilizers and the ABS phase and thus the obtained compatibilized PLLA/ABS blends display a fine cocontinuous morphology and excellent mechanical properties. For the other two ABS materials, which are constituted by St, AN, and BD, it has been found that the PMMA‐type compatibilizers are pulled out from the interface to form micelles in the PLLA phase, on account of the weakening interactions between ABS and PMMA‐type compatibilizers. The thus formed micelles can interact with the crystallization of PLLA and the melting temperature ( T m ) of PLLA is split into a lower and a higher peak firstly, compared to the T m of neat PLLA, then significantly decrease to lower temperature, with increasing the amount of micelles in the PLLA phase. © 2020 Wiley Periodicals, Inc. J. Polym. Sci. 2020, 58, 372–382 Abstract : The PMMA‐type and comb‐like polymer, which reacts with PLLA at the interface of PLLA/ABS, is drawn into the PLLA phase to form micelles because of the unbalanced forces at the interface. The thus formed micelles interact with the molecular chains of PLLA; the T m (PLLA) in the PLLA/ABS blend is at first split into a lower and a higher peak when compared to the T m of neat PLLA, then significantly decreases to a lower temperature upon increasing the amount of micelles.